Fighting the Learning Crisis in Developing Countries: A Randomized Experiment of Self-Learning at the Right Level - Sawada, Yasuyuki; Kawarazaki, Hikaru; Mahmud, Minhaj; Seki, Mai (Economic Development and Cultural Change, 2024)
This study investigates the effectiveness of a globally popular method of self-learning at the right level in improving learning outcomes-the cognitive and noncognitive abilities of disadvantaged students-in a developing country, Bangladesh. Using a randomized controlled trial design, we find substantial improvements in cognitive abilities measured by math test scores and in catch-up effects in terms of noncognitive abilities or personality traits measured through a self-esteem scale. Moreover, our study is, to our knowledge, the first to use alternative cognitive ability measures, that is, time reduction as well as time-adjusted test score, which are critical dimensions of cognitive development. Subsequently, we investigate the long-term effects using students' math results in the national-level exam. We find a reasonable longer-term effect on cognitive abilities 20 months after the intervention for younger students. Our estimates indicate that the program's benefits exceed its costs.
Keywords: Cognitive and Noncognitive; Learning Crisis; Personality Traits; Self-Learning; Developing Countries